SOME ISSUES OF UZBEK TERMINOLOGY IN THE ERA OF GLOBALIZATION - A. Usmanov (Modern American Journals, 2026)
The process of globalization has a great impact on Uzbek terminology, as new scientific, technical and social terms are mastered from foreign languages. This situation creates problems with the standardization and adaptation of terms to the national language.